Volatilty and electoral competitivity in Latin America: an exploratory study of six party systems (Colección, 2017)
To what extent electoral volatility and party system competitiveness may be related? This paper seeks to answer this question by studying six Latin American party systems (Brazil, Chile, Ecuador, Peru, Uruguay and Venezuela). Considering Presidential and legislative elections since the return to democracy in each of these countries, we developed a tipology of party systems: volatile competitive, volatile uncompetitive, stable competitive and stable uncompetitive. Therefore, we detect patterns of change and continuity in its competitive dynamics
Keywords: Electoral volatility; Electoral competitiveness; Party systems; Latin America; Institutionalization